(untitled) (Applied Biological Research, 2018)
The present study was aimed to evaluate the toxicological effect on antioxidant defense system in Monopterus cuchia induced by commercial formulation of Glyphosate EXCEL MERA 71. In the study, fish were exposed to sub-lethal concentrations of 1 and 2 mg L-1. LC50 value for glyphosate at 96 h exposure could not be determined because no fish mortality was observed even at the maximum concentration tested 200 mg L-1. After 6, 24, 96 and 168 h of exposure, there were significant decrease in the level of red blood cells, haemoglobin concentration and a significant increase in white blood cells count in both treated groups. The enzyme alanine aminotransferase decreased whereas aspartate aminotransferase and alkaline phosphatase showed increase in comparisonto control which were analyzed in serum. The fish showed transient decrease in superoxide dismutase and catalase activities and the non-enzymatic antioxidant reduced glutathione showed repressed activity after glyphosate exposure. However, glutathione-S-transferase activity significantly increased in kidney and intestine and decreased in liver in treated groups. Moreover, the present study also investigated the possible stimulation of heat shock protein 70 (Hsp70) mRNA and glyphosate exposure led to a significant increase in the levels of mRNA transcript in liver and kidney.